2007
DOI: 10.1126/science.1143320
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on "A G Protein–Coupled Receptor Is a Plasma Membrane Receptor for the Plant Hormone Abscisic Acid"

Abstract: Our study provided experimental evidence that GCR2 is a membrane-associated abscisic acid receptor that interacts with the G protein a subunit GPA1 in Arabidopsis. Although we cannot rule out GCR2 as a lanthionine synthetase homolog, our data indicate that it may define a new type of nonclassical G protein-coupled receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…A plasma membranelocalized, putative G protein-coupled receptor has also been proposed to be an ABA receptor (X. Liu et al, 2007aLiu et al, , 2007b, in addition to the two soluble ABAbinding proteins, the Mg-chelatase and the FCA RNAbinding protein (Razem et al, 2006;Shen et al, 2006).…”
Section: Atpub Proteins and S-domainmentioning
confidence: 99%
“…A plasma membranelocalized, putative G protein-coupled receptor has also been proposed to be an ABA receptor (X. Liu et al, 2007aLiu et al, , 2007b, in addition to the two soluble ABAbinding proteins, the Mg-chelatase and the FCA RNAbinding protein (Razem et al, 2006;Shen et al, 2006).…”
Section: Atpub Proteins and S-domainmentioning
confidence: 99%
“…ABA signal transduction has been extensively studied, and numerous signaling components, including ABA receptors, have been identified (reviewed in Finkelstein and Rock 2002; Cutler et al 2010). A putative G-protein-coupled receptor GCR2 and GPCR-type G proteins GTG1 and GTG2 have been reported as candidate plasma membrane-type ABA receptors (Liu et al 2007a, b; Johnston et al 2007; Pandey et al 2009), though it is controversial whether GCR2 regulates ABA-mediated inhibition of seed germination and post-germination growth (Gao et al 2007; Guo et al 2008). GTGs are positively involved in ABA signaling and interacts with the sole Arabidopsis G protein α subunit GPA1 (Pandey and Assmann 2004), which inhibits the activity of GTG-ABA binding to negatively regulate ABA signaling (Pandey et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…ABA signal perception, which has been considered to be mediated by multiple receptors, including plasma membrane and intracellular receptors (for review, see Assmann, 1994;, has attracted much attention. In recent years, two classes of plasma membrane ABA receptors, an unconventional G-protein-coupled receptor (GPCR), GCR2, and a novel class of GPCR, GTG1 and GTG2, that regulate the major ABA responses in seed germination, seedling growth, and stomatal movement (Johnston et al, 2007;Liu et al, 2007aLiu et al, , 2007bPandey et al, 2009), have been reported. However, whether GCR2 regulates ABA-mediated seed germination and postgermination growth is controversial, because the ABA-related phenotypes are weak to absent in gcr2 mutants Guo et al, 2008).…”
mentioning
confidence: 99%